Relations with wildlife of Wichi and Criollo people of the Dry Chaco, a conservation perspective - Camino, Micaela; Cortez, Sara; Altrichter, Mariana; Matteucci, Silvia Diana (Ethnobiology and Conservation, 2018)
Indigenous Wichís and mestizos Criollos inhabit a rural, biodiversity rich, area of the Argentinean Dry Chaco. Traditionally, Wichís were nomads and their relations with wildlife were shaped by animistic and shamanic beliefs. Today, Wichís live in stable communities and practice subsistence hunting, gathering and in some cases, fishing. Criollos are mestizos, i.e. a mixture of the first Spanish settlers and different indigenous groups. They arrived during the 20th century from neighbouring Provinces. They practice extensive ranching, hunting and gathering. Our aim was to help develop effective and legitimate actions to conserve wildlife species in this region, focused on Wichís´ and Criollos´ perceptions of and relations with wildlife. We conducted semi-structured interviews (N=105) in rural settlements. We found differences in both groups´ hunting techniques, drivers and perceptions on the importance of wild meat for nutrition. However, both groups have a close relation with wildlife, they use wild animals in a variety of ways, including as food resource, medicine and predictors of future events. Wichís and Criollos also relate with wildlife in a spiritual dimension, have animistic and shamanic beliefs and have unique traditional ecological knowledge. Hunters in both communities are breaking traditional hunting norms but conservation measures grounded on these norms have a higher probability of success. Management recommendations include developing programmes focused on (i) conserving thin armadillos; (ii) conserving pregnant and breeding females of all species; (iii) managing dogs to avoid unnecessary killings and on (iv) improving local livelihoods. We also provide recommendations that are specific for each group.